A customer service representative job not for the faint-hearted - Daily Express, (KK) (Daily Express (kk), 2017)
KUALA LUMPUR: "Do you know t hai this is urgent? Do you even know what I want'/ Or you're just plain stupid to understand anything? You can't even do a simple customer service job !"These are the nasty lines that Zati Farhana Zulkarnain has come across many times as a customer service representative.